Elemental Analysis of Some Libyan Medicinal Plants Using Inductively Coupled Plasma Atomic Emission Spectroscopy - Saleh A Ouheda; Toraia M Takteek; Fawzeya Gharghar (African Journal of Advanced Pure and Applied Sciences, 2025)
The elemental compositions of four medicinal plants grown in Libyan wilderness, particularly Juniperus Communis, Globularia alypum, Origanun majorana and Ajuga Iva, have been analyzed using four different approaches. All plant samples were analyzed for 18 elements (Ca, Mg, K, Na, P, Fe, Si, Mn, Zn, Cu, Co, Cr, Ni, Sn, Al, Hg, Pb and Cd) by ICP-MS technique .The macronutrients, calcium, magnesium, potassium, sodium, phosphorus and iron are found to be the dominate species in the selected samples ranging from calcium which has the highest concentration to iron with the lowest content. The data also demonstrated that the highest micronutrient concentrations were observed for silicon, manganese, and zinc, respectively. The concentration level of aluminum is considered to be relatively high compared with other toxic elements which could be due to the high soil and environmental content of this element or may be due to the much higher selectivity of these plants towards aluminum. A variety of statistical methods such as Principal Component Analysis (PCA), Partial Least Squares Discriminant Analysis (PLS-DA), Hierarchical Cluster Analysis (HCA), and boxplot graphical tool were applied to examine the significant differences between the selected medical plants regarding their elemental composition, as well as to identify variations arising from different sample preparation methods. In these all, the statistical analysis revealed significant differences in yield between the water extraction procedure and other extraction methods, a discrepancy that can be explained by the limited solubility of the corresponding water-soluble salts. Meanwhile there is a slight difference between ashing method and other two methods (HNO3/H2O2 and HNO3/HClO4 methods). In general, the concentration ranges obtained using (HNO3/HClO4) acid mixture is a bit higher compared to (HNO3/H2O2) and dry ashing methods.